Team Co-occurence in Internet Search Engine Queries: An Analysis of the Excite Data Set - Wolfram, Dietmar (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Unique queries submitted to the Excite search engine were analyzed for empirical regularities in the co-occurrence of search terms. The distribution of frequency of term pair occurrences was fitted to three models used in informetric studies to determine whether the pattern of term usage followed a Zipfian distribution. Relatively poor fits were obtained for two of the models tested. . .